2010
DOI: 10.1088/0022-3727/43/30/305201
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of fast electrons in a subnanosecond breakdown of air-filled diodes at atmospheric pressure

Abstract: In this work, the spectra of electron beams produced in air-filled diodes at atmospheric pressure were studied for different cathode designs. The feasibility of correct reconstruction of the electron beam spectrum from an experimental dependence of its attenuation factor in foils of different thicknesses was demonstrated. The electron energy distributions were calculated on minimum a priori assumptions by regularization of an ill-posed problem—a Fredholm integral equation. The spectra of a subnanosecond electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 24 publications
3
27
0
2
Order By: Relevance
“…Thus, the total yield is estimated to be 2·10 9 fast electrons per pulse. This value agrees well with typical experiment data [5,16,17].…”
Section: Momentum Of Electrons (P/mc)supporting
confidence: 93%
See 2 more Smart Citations
“…Thus, the total yield is estimated to be 2·10 9 fast electrons per pulse. This value agrees well with typical experiment data [5,16,17].…”
Section: Momentum Of Electrons (P/mc)supporting
confidence: 93%
“…This is clear because in our model of axisymmetric discharge all the electrons generated in the amplified field on the ionization wave front, while in real discharges only a small group of particles participate in this interaction with field wave [5].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Generally, the generation RAEs consists of four main stages: (i) the appearance of initial electrons, (ii) the mode transition into runaway electrons for part electrons, (iii) the generation of general RAEs, (iv) the ionization wave front arrival at the anode [1,7,13,15,19]. In the first stage, when the nanosecond high-voltage pulses are applied on the cathode, the electric field strength achieves sufficient value (>10 7 V=m) at the macro-and micro-inhomogeneities of the cathode, resulting in the appearance of initial electrons near the cathode and the development of electron avalanches.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Tarasenko et al achieved some different experimental results on RAEs. It was found that there were two or three groups of electrons with different energies in the RAE beam obtained downstream from the anode foil [13][14][15]. Moreover, under an optimal condition, the quantity of electrons with the anomalous energy was not more than 10% of the total number of the RAEs.…”
Section: Introductionmentioning
confidence: 99%